Turning the tables on cytomegalovirus: targeting viral Fc receptors by CARs containing mutated CH2-CH3 IgG spacer domains - Proff, Julia; Brey, Charlotte U.; Enßer, Armin; Holter, Wolfgang; Lehner, Manfred (Journal of Translational Medicine, 2018)
Background: During infection with human cytomegalovirus (HCMV) several viral proteins occur on cell surfaces in high quantity. We thus pursue an HLA-independent approach for immunotherapy of HCMV using chimeric antigen receptors (CARs) and bispecific -BiTE (R) antibody constructs. In this context, HCMV-encoded proteins that mediate viral immune evasion and bind human IgG might represent particularly attractive target antigens. Unlike in observations of similar approaches for HIV and hepatitis B and C viruses, however, HCMV-infected cells develop a striking resistance to cytotoxic effector functions at later stages of the replication cycle. In our study we therefore wanted to test two hypotheses: (1) CAR T cells can efficiently inhibit HCMV replication independently from cytotoxic effector functions, and (2) HCMV can be targeted by CH2-CH3 IgG spacer domains that contain mutations previously reported to prevent exhaustion and to rescue CAR T cell function in vivo. Methods: Replication of GFP-encoding recombinant HCMV in fibroblasts in the presence and absence of supernatants from T cell co-cultures plus/minus cytokine neutralizing antibodies was analyzed by flow cytometry. CARs with wild type and mutated CH2-CH3 domains were expressed in human T cells by mRNA electroporation, and the function of the CARs was assessed by quantifying T cell cytokine secretion. Results: We confirm and extend previous evidence of antiviral cytokine effects and demonstrate that CAR T cells strongly block HCMV replication in fibroblasts mainly by combined secretion of IFN-gamma and TNF. Furthermore, we show that fibroblasts infected with HCMV strains AD169 and Towne starting from day 3 have a high capacity for binding of human IgG1 and also strongly activate T cells expressing a CAR with CH2-CH3 domain. Importantly, we further show that mutations in the CH2-CH3 domain of IgG1 and IgG4, which were previously reported to rescue CAR T cell function by abrogating interaction with endogenous Fc receptors (FcRs), still enable recognition of FcRs encoded by HCMV. Conclusions: Our findings identify HCMV-encoded FcRs as an attractive additional target for HCMV immunotherapy by CARs and possibly bispecific antibodies. The use of specifically mutated IgG domains that bind to HCMV-FcRs without recognizing endogenous FcRs may supersede screening for novel binders directed against individual HCMV-FcRs.
EVALuna2:35288